Peripheral blood B-cell compartment dysregulation in multidrug-resistant tuberculosis is associated with reduced circulating marginal zone-like B cells - Liu, Mei; Wen, Junjie; Gao, Qin; Xu, Tao; Lan, Yuanbo; Meng, Lu (Frontiers in Immunology, 2026)
ObjectiveMultidrug-resistant tuberculosis (MDR-TB) remains a major global health challenge. While T cell-mediated immunity in tuberculosis is well characterized, alterations in circulating B-cell subsets during chronic MDR-TB are less well defined.MethodsPeripheral blood mononuclear cells (PBMCs) from healthy controls [interferon gamma release assay negative (IGRA−)], individuals with latent tuberculosis infection (LTBI; IGRA+), and patients with active tuberculosis (ATB) were analyzed using multiparameter flow cytometry panels. Major lymphoid and myeloid populations and detailed B-cell subsets were quantified.ResultsFrequencies of major T-cell and natural killer (NK)-cell populations were broadly similar across groups. In contrast, patients with ATB showed a reduction in total CD19+ B cells. Within the B-cell compartment, ATB was characterized by an increased proportion of naïve B cells and a pronounced reduction in antibody-secreting cells (ASCs). Circulating marginal zone-like B cells (MZ B, IgD+IgM+CD27+) were also reduced in ATB compared with non-ATB groups. Receiver operating characteristic (ROC) analysis suggested that reduced MZ B-cell frequency may help discriminate individuals with ATB from those without ATB; however, this observation should be interpreted as exploratory given the cohort size and composition.ConclusionMDR-TB is associated with broad perturbations of the peripheral B-cell compartment, including reduced ASCs and decreased circulating MZ B cells. These findings highlight B-cell dysregulation as a feature of active disease and identify MZ B cells as a subset of interest for further investigation rather than as a stand-alone diagnostic marker.